Phenotypic plasticity and community composition interactively shape trophic interactions. Issue 8 (26th April 2020) - Start, Denon
Abstract : Trait variation defines and underpins biodiversity, yet we are only beginning to understand how processes acting across biological scales (individuals to whole communities) interact to produce trait differences and their consequences, particularly over short time scales. First, species often differ widely in their mean phenotype, meaning that changes in community composition can alter average trait values of a guild. Second, phenotypic plasticity alters the trait values of individuals, and the net effect of plasticity can also shift the average trait values of a specific species or of whole communities. However, community assembly, phenotypic plasticity, and their effects on biological patterns are not independent. The expression of phenotypic plasticity tends to be species‐specific, meaning that differences in species' relative abundances will shape trait change and resulting ecological patterns and processes. I test this idea using mesocosms and simulations of communities of dragonfly larvae that differ in activity rate. Some but not all species reduced their activity rate in response to predation risk, causing larger trait‐mediated changes in trophic interactions in experimental communities dominated by plastic versus aplastic species. Using surveys and simulations of natural ponds, I demonstrate that community composition will shape patterns of phenotypic plasticity, with likely consequences for ecological dynamics in the wild. The interactive effects of trait differences across scales of biological organization necessitates an integrated view of diverse biological processes, including plasticity and community assembly, in order to understand ecological interactions.